Systematic study of the effect of short range correlations on the form factors and densities of s-p-d shell nuclei - Moustakidis, H. C.; Massen, S. E. (HNPS Advances in Nuclear Physics, 2020)
Analytical expressions of the one- and two-body terms in the cluster expansion of the charge form factors and densities of the s-p and s-d shell nuclei with N=Z are derived. They depend on the harmonic oscillator parameter 6 and the parameter β which originates from the Jastrow correlation function. These expressions are used for the systematic study of the effect of short range correlations on the form factors and densities and of the mass dependence of the parameters ò and β. These parameters have been determined by fit to the experimental charge form factors. The inclusion of the correlations reproduces the experimental charge form factors at the high momentum transfers (q > 2 fm^-1). It is found that while the parameter β is almost constant for the closed shell nuclei, 4He, 16O and 40Ca, its values are larger (less correlated systems) for the open shell nuclei, indicating a shell effect in the closed shell nuclei.